Quantitative Mass Spectrometry Reveals Partial Translational Regulation for Dosage Compensation in Chicken - Uebbing, Severin (Mol Biol Evol, 2015)
There is increasing evidence that dosage compensation is not a ubiquitous feature following sex chromosome evolution, especially not in organisms where females are the heterogametic sex, like in birds. Even when it occurs, compensation can be incomplete and limited to dosage-sensitive genes. However, previous work has mainly studied transcriptional regulation of sex-linked genes, which may not reflect expression at the protein level. Here, we used liquid chromatography–tandem mass spectrometry to detect and quantify expressed levels of more than 2,400 proteins in ten different tissues of male and female chicken embryos. For comparison, transcriptome sequencing was performed in the same individuals, five of each sex. The proteomic analysis revealed that dosage compensation was incomplete, with a mean male-to-female (M:F) expression ratio of Z-linked genes of 1.32 across tissues, similar to that at the RNA level (1.29). The mean Z chromosome-to-autosome expression ratio was close to 1 in males and lower than 1 in females, consistent with partly reduced Z chromosome expression in females. Although our results exclude a general mechanism for chromosome-wide dosage compensation at translation, 30% of all proteins encoded from Z-linked genes showed a significant change in the M:F ratio compared with the corresponding ratio at the RNA level. This resulted in a pattern where some genes showed balanced expression between sexes and some close to 2-fold higher expression in males. This suggests that proteomic analyses will be necessary to reveal a more complete picture of gene regulation and sex chromosome evolution.